FACTORS RELATED TO THE INCIDENCE OF LBW (LOW BIRTH WEIGHT) IN TANJUNG PURA REGIONAL HOSPITAL, TANJUNG PURA DISTRICT, LANGKAT REGENCY YEAR 2023 - Ummu Humairah Br Sitepu; Sonia Novita Sari; Ade Rachmat Yulianto; Kamelia Sinaga; Kezia S.A Rajagukguk; Erna Wati Sinaga; Yudha Anggriani Putri Nasution, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Birth weight is the baby's weight measured within the first hour after birth. It also helps assess growth and gestational age, as well as maturity. According to the WHO, low birth weight (LBW) is defined as a newborn weighing less than 2,500 grams. LBW can occur not only in premature babies but also in full-term babies who experience growth restriction during pregnancy.Purpose: To determine the factors associated with the incidence of low birth weight (LBW) at Tanjung Pura Regional Hospital in 2023. Population and sample: The case population was all mothers who gave birth to babies at Tanjung Pura Regional General Hospital in May-June 2023. Based on data obtained from medical records at Tanjung Pura Regional General Hospital in 2023, there were 39 people. Place and Time: inTanjung Pura Regional Hospital, Tanjung Pura District, Langkat Regency. Results : The results of statistical analysis using the chi square test stated that there was a relationship between maternal age and the incidence of LBW at Tanjung Pura Regional Hospital in 2023 with a p-value of 0.020 (p-value <0.05).Bivariate : The bivariate analysis in this study uses the chi-square test at a 95% confidence level to analyze the relationship between the independent variables and the dependent variable. If the analysis results show a significant relationship with a p-value <α (0.05), CONCLUSION : There is a relationship between maternal age and the incidence of LBW inTanjung Pura Regional Hospital in 2023.There is a relationship between maternal parity and the incidence of LBW in Tanjung Pura Regional Hospital in 2023.